Case Study Of PT. Media Teknologi Informasi (SDA ASIA) - Sosiawan, Norma (2007)
This case study tries to analyze a business of PT.Media Teknologi Informasi (MTI) as a part of an S&S Media Group (Europe),which was basically generated by information technology industry development.